Long-Term Otitis Media Outcomes in Infants With Early Tympanostomy Tubes. (December 2020) - Luu, Kimberly; Park, James; Shaffer, Amber D.; Chi, David H.
Objective: To review the otologic outcomes of infants who failed the newborn hearing screen (NBHS) and received early tympanostomy tubes for otitis media with effusion (OME). Study Design: Retrospective case series. Setting: Tertiary care pediatric hospital. Subjects and Methods: Consecutive patients (2007-2018) who failed an NBHS and required tympanostomy tubes before 6 months of age were included. Variables including hearing loss and otitis media risk factors, episodes of acute otitis media (AOM), number of subsequent tympanostomy tubes, and posttympanostomy tube audiogram results were recorded. Results: The cohort included 171 patients. Median age at referral to otolaryngology was 2.7 months. Sensorineural hearing loss (SNHL) was subsequently identified in 22 (12.9%) of infants after resolution of the effusion. The peak incidence of AOM was during the second year of life (1-1.9 years), with a median of 1 episode. Ninety-five patients (55.6%) had replacement of tubes, 41 of 171 (24.0%) had 2 or more additional sets of tubes, and long-term tubes were eventually placed in 8 of 95 (8.4%) patients. Craniofacial anomalies were identified in 43.3% of patients. Tube replacement (hazard ratio, 3.00; 95% CI, 1.95-4.63; P < .01, log-rank) and AOM (β, 1.04; 95% CI, 0.43-1.65; P = .04, ordered logistic regression) were more common, and SNHL less common (odds ratio, 0.17; 95% CI, 0.031-0.61; P < .01, logistic regression), in children with craniofacial anomalies. Conclusion: OME is a common cause of failed NBHS. A notable proportion was subsequently found to have SNHL, reiterating the need for postoperative hearing assessments. Infants meeting indication for early tympanostomy tubes for resolution of OME have a high incidence of recurrent AOM and require subsequent tubes.